Membrane-Initiated Estradiol Signaling Regulating Sexual Receptivity - Micevych, Paul E.; Dewing, Phoebe (Frontiers in Endocrinology, 2011)
Estradiol has profound actions on the structure and function of the nervous system. In addition to nuclear actions that directly modulate gene expression, the idea that estradiol can rapidly activate cell signaling by binding to membrane estrogen receptors (mERs) has emerged. Even the regulation of sexual receptivity, an action previously thought to be completely regulated by nuclear ERs, has been shown to have a membrane-initiated estradiol signaling (MIES) component. This highlighted the question of the nature of mERs. Several candidates have been proposed, ERα, ERβ, ER-X, GPR30 (G protein coupled estrogen receptor; GPER), and a receptor activated by a diphenylacrylamide compound, STX. Although each of these receptors has been shown to be active in specific assays, we present evidence for and against their participation in sexual receptivity by acting in the lordosis-regulating circuit. The initial MIES that activates the circuit is in the arcuate nucleus of the hypothalamus (ARH). Using both activation of μ-opioid receptors (MOR) in the medial preoptic nucleus and lordosis behavior, we document that both ERα and the STX receptor participate in the required MIES. ERα and the STX receptor activation of cell signaling are dependent on the transactivation of type 1 metabotropic glutamate receptors (mGluR1a) that augment progesterone synthesis in astrocytes and protein kinase C (PKC) in ARH neurons. While estradiol-induced sexual receptivity does not depend on neuroprogesterone, proceptive behaviors do. Moreover, the ERα and the STX receptor activation of medial preoptic MORs and augmentation of lordosis were sensitive to mGluR1a blockade. These observations suggest a common mechanism through which mERs are coupled to intracellular signaling cascades, not just in regulating reproduction, but in actions throughout the neuraxis including the cortex, hippocampus, striatum and DRGs.